2015
DOI: 10.1016/j.jnoncrysol.2014.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Infrared-transparent glass ceramics: An exploratory study

Abstract: a b s t r a c tIn this work, the vision and need for a fully ceramized long-wave infrared (LWIR)-transmitting glass ceramic have been articulated. Three sulfide systems were explored including two with La 2 S 3 in hopes of imparting strong bonds from this refractory sulfide, and two containing GeS 2 in hopes of widening the glass-forming region. Attempts were made to produce glasses in the Ga 2 S 3 -La 2 S 3 -(ZnS,CaS) system, the GeS 2 -La 2 S 3 system, and the GeS 2 -Ga 2 S 3 -CdS system. Water quenching pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Numerous references describe how this has been employed in commercial applications. (11)(12)(13)(14)(15) Phase separation effects are of general interest in glass science, as it can give rise to pronounced changes in physical, thermal and optical properties of network glasses which may be useful or detrimen-tal. (16,17) Detailed characteristics of phase separated glasses depend strongly on the nature and volume fraction of the phases developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous references describe how this has been employed in commercial applications. (11)(12)(13)(14)(15) Phase separation effects are of general interest in glass science, as it can give rise to pronounced changes in physical, thermal and optical properties of network glasses which may be useful or detrimen-tal. (16,17) Detailed characteristics of phase separated glasses depend strongly on the nature and volume fraction of the phases developed.…”
Section: Introductionmentioning
confidence: 99%
“…(19) Related efforts examining infrared (IR) glass-ceramics have been reported which may or may not (deliberately) exploit phase separation as a stepping stone to controlled crystallization. (13,14,20) Oxide and non-oxide glasses possess compositions known to exhibit phase separation, though literature on specific aspects in non-oxide systems (such as phase diagrams and immiscibility boundaries) is limited with a few noteworthy exceptions. (21) As discussed below, such glass compositions possess large, positive enthalpies of mixing in the liquid state resulting in instability that can vary with composition.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been also focused on the preparation of GCs transparent up to 12 µm using chalcogenide glasses. The crystallization of chalcogenide glasses has been of great interest [168][169][170][171][172][173][174]. However, the crystallization of these glasses is difficult to control, as reported in [173]; Zhang et al reported that, as for oxide glasses, the control of the nucleation and crystal growth is very sensitive to temperature and to the glass composition.…”
Section: Glass-ceramics Fibersmentioning
confidence: 99%
“…The main limitation in realizing a greater number of candidate glass families suitable for controlled crystallization is poor glass-forming ability and the change in optical properties when a nucleating agent is introduced [4]. The addition of nucleating agents has been shown to result in undesirable effects such as phase separation, spontaneous crystallization of the entire glass upon cooling, as well as reduced crystal growth control [23]. Some groups have investigated the formation of GCs in ChGs to increase mechanical hardness and toughness [17,[24][25][26][27][28][29][30][31][32], but a systematic correlation between starting glass morphology (homogeneous glass versus phase separated glass) and glass-crystal volume fractions in a GC, and the respective corresponding impact on the mechanical properties of ChG ceramics, has not to our knowledge been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have focused on the measurement of the glass and GC's micro-indentation response as quantified by Vickers hardness, and a variation in the materials Young's modulus following heat-treatment. A multicomponent ChG is the subject of the study, GeSe 2 -As 2 Se 3 -PbSe (GAP-Se), which possesses good transparency in the IR region and exhibits the requisite narrow size distribution of the secondary crystallized phase(s) making it suitable as an optical nanocomposite [23,35,41]. Such behavior enables the use of a controlled crystallization protocol to realize high RI nanocrystals for GRIN applications.…”
Section: Introductionmentioning
confidence: 99%